Analysis of the Influence of ShopeeFood Services on Customer Loyalty of Pempek Checklist using the E-Service Quality Model - Dio Rizqy Saputra; Apriansyah Putra; Rizka Dhini Kurnia; Putri Eka Sevtiyuni (SISTEMASI, 2026)
The rapid advancement of information and communication technology in the digital era has transformed consumer behavior, enabling people to fulfill their daily needs more quickly and conveniently through application-based platforms. One notable development is the widespread adoption of online food delivery services such as ShopeeFood, which offer convenience, speed, and a variety of features that support digital transactions. This trend has the potential to influence customer loyalty toward food service businesses, particularly through the quality of electronic services provided. This study aims to examine the effect of E-Service Quality on customer loyalty toward Pempek Checklist using the E-Service Quality model. A quantitative research approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Data were collected through an online questionnaire from 100 customers who had previously purchased Pempek Checklist through ShopeeFood. The results indicate that the Efficiency, Fulfillment, and Privacy dimensions have positive and significant effects on customer loyalty, whereas System Availability does not have a significant effect. Collectively, the four dimensions explain customer loyalty with an R² value of 0.967, indicating very strong explanatory power. These findings suggest that, in the context of ShopeeFood services, customer loyalty is driven primarily by ease of use, reliable service fulfillment, and transaction security rather than by system availability. The study highlights the importance for both business owners and platform providers to continuously enhance electronic service quality in order to strengthen long-term customer loyalty.